Development of an intervention program to increase effective behaviours by patients and clinicians in psychiatric services: Intervention Mapping study - Schene Aart; van Meijel Berno; Koekkoek Bauke; Hutschemaekers Giel (BMC, 2010)
Abstract Background Health clinicians perceive certain patients as 'difficult' across all settings, including mental health care. In this area, patients with non-psychotic disorders that become long-term care users may be perceived as obstructing their own recovery or seeking secondary gain. This negative perception of patients results in ineffective responses and low-quality care by health clinicians. Using the concept of illness behaviour, this paper describes the development, implementation, and planned evaluation of a structured intervention aimed at prevention and management of ineffective behaviours by long-term non-psychotic patients and their treating clinicians. Methods The principles of Intervention Mapping were applied to guide the development, implementation, and planned evaluation of the intervention. Qualitative (individual and group interviews), quantitative (survey), and mixed methods (Delphi-procedure) research was used to gain a broad perspective of the problem. Empirical findings, theoretical models, and existing evidence were combined to construct a program tailored to the needs of the target groups. Results A structured program to increase effective illness behaviour in long-term non-psychotic patients and effective professional behaviour in their treating clinicians was developed, consisting of three subsequent stages and four substantial components, that is described in detail. Implementation took place and evaluation of the intervention is being carried out. Conclusions Intervention Mapping proved to be a suitable method to develop a structured intervention for a multi-faceted problem in mental health care.